Divergent tissue and sex effects of rapamycin on the proteasome-chaperone network of old mice - Rodriguez, Karl A.; Dodds, Sherry G.; Strong, Randy; Galvan, Veronica; Sharp, Z. D.; Buffenstein, Rochelle (Frontiers in Molecular Neuroscience, 2014)
Rapamycin, an allosteric inhibitor of the mTOR kinase, increases longevity in mice in a sex-specific manner. In contrast to the widely accepted theory that a loss of proteasome activity is detrimental to both life- and healthspan, biochemical studies in vitro reveal that rapamycin inhibits 20S proteasome peptidase activity. We tested if this unexpected finding is also evident after chronic rapamycin treatment in vivo by measuring peptidase activities for both the 26S and 20S proteasome in liver, fat, and brain tissues of old, male and female mice fed encapsulated chow containing 2.24mg/kg (14 ppm) rapamycin for 6 months. Further we assessed if rapamycin altered expression of the chaperone proteins known to interact with the proteasome-mediated degradation system (PMDS), heat shock factor 1 (HSF1), and the levels of key mTOR pathway proteins. Rapamycin had little effect on liver proteasome activity in either gender, but increased proteasome activity in female brain lysates and lowered its activity in female fat tissue. Rapamycin-induced changes in molecular chaperone levels were also more substantial in tissues from female animals. Furthermore, mTOR pathway proteins showed more significant changes in female tissues compared to those from males. These data show collectively that there are divergent tissue and sex effects of rapamycin on the proteasome-chaperone network and that these may be linked to the disparate effects of rapamycin on males and females. Further our findings suggest that rapamycin induces indirect regulation of the PMDS/heat-shock response through its modulation of the mTOR pathway rather than via direct interactions between rapamycin and the proteasome.